Liberia : A Diagnostic of Social Protection - Borgarello, Andrea; Figazzolo, Laura; Weedon, Emily (World Bank, Washington, DC, 2014)
Safety Nets are limited in Liberia and, although as a share of GDP, expenditures are higher than the regional average, the average benefit amount is equal to only 7-20 percent of the poverty line. The current system focuses on the country s most vulnerable populations but that the system is fragmented. Food insecurity is mainly addressed through food transfers aimed at preventing starvation and malnutrition. Unemployed people, including the large portion of the population engaged in informal employment, are targeted primarily by public works. Scaling-up Liberia s safety nets would require significant investments, which are not viable at the moment given the country s financial constraints. Efforts should hence focus on improving the overall safety net system within the existing budget.